Conjugated polymer, preparation method and applications thereof - ZHOU MINGJIE; GUAN RONG; LI MANYUAN (2014)
The invention relates to a conjugated polymer represented by the formula (P), wherein the R1 represents an alkyl group with a carbon number of 1 to 16, the R2 represents an alkyl group with a carbon number of 1 to 16, the R3 and R4 are respectively represent an H atom or an alkyl group with a carbon number of 1 to 12, and n is a natural number in a range of 5 to 60. The invention also relates to a preparation method and applications of the conjugated polymer. Pyrroloindolodithiophene derivatives taken as the donor unit and a strong acceptor unit (diketopyrrolopyrrole) are bridged and copolymerized through selenophene, thus the energy gap of the conjugated copolymer is reduced through the interactive reactions (electron pushing and pulling effect) between the acceptor unit and the donor unit, and the light absorption range of the material is greatly enlarged. Through selecting the novel donor unit and acceptor unit, a D-pi-A type conjugated polymer containing a unit of pyrroloindolodithiophene-selenophene-dike